Analysis Of The Effectiveness Of The Criminal Justice System In Dealing With Cybercrime In The Digital Era - Fadli Faisal Rasyid; Sitti Harlina; Nurasia Natsir (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
This research aims to analyze the criminal justice system's effectiveness in dealing with cybercrime in the digital era. Given the rapid increase in cybercrime, this research explores how the criminal justice system responds to and adapts to these new challenges. Through qualitative and quantitative analysis, this research assesses how the criminal justice system can prevent, detect, and prosecute cybercrime. Factors such as legal policy, law enforcement capabilities, and international cooperation are considered in this assessment. The results of this research are expected to provide valuable recommendations and strategies for enhancing the criminal justice system's effectiveness in dealing with cybercrime and insights into the challenges and opportunities in this digital era.